Insights Into Early Childhood English Education: A Comparative Analysis of Perspectives Between English Teachers and Preschool Teachers - Özütler, Nisa Nur; Demir, Ebiha; YAĞAN, SEVCAN (Routledge, 2024)
The study aims to illuminate and compare of the perceptions of Turkish preschool and EFL teachers regarding English language education in the preschool years. The study is a basic qualitative research method involving 16 Turkish EFL and Turkish preschool teachers. As a result, the teachers showed similar views about early English education benefits a child’s language, cognitive, and socio-emotional development. However, both groups expressed dissatisfaction with the quality of early English education, highlighting the challenges. Teachers emphasized that English language should be taught by native Turkish speakers rather than native English speakers. © 2024 ASPE.
Keywords: Early Childhood Period; EFL Teachers; English Education in Preschool; English Language Education; Preschool Teachers